A STUDY ON FORMULATION AND ACCEPTABILITY OF ANTI-COLD MOCKTAILS WITH VITAMIN C ENRICHED INGREDIENTS - A, Arun; X, Disalva; M, Murali (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Common cold is a widespread respiratory infection among all age groups. This creates a great nuisance and discomfort making a person feels ill. Common cold can also be treated with home-made remedies. The study gives attention to develop and formulate Mocktail drinks with Vitamin C enriched ingredients to fight against cold. Method: Developed Mocktails are tested for the presence of vitamins, and evaluated with sensory evaluation among 50 panelist members, feedback data collected are analyzed with statistical software SPSS (21.0). Results: The study exhibits that the formulated recipes of Mocktails are identical in aroma analysis with one-way ANOVA test proves, the recipes are significantly different in taste and appearance. The Freidman's test shows that the Mocktail with pineapple juice (Code C) is more preferred by panelist members. Conclusion: The developed Mocktail recipes are rich in Vitamin C and significantly different in their organoleptic parameters furthermore preferably acceptable. Â